Combination of Transverse Mode Selection and Active Longitudinal Mode-Locking of Broad Area Semiconductor Lasers. (10th July 2014) - Doering, Christoph; Fouckhardt, Henning
Abstract : Experimental results of the combination of transverse mode selection and active mode-locking with anti-reflection-coated broad area lasers (BALs) are presented. The BALs are subject to feedback from a free-space external Fourier-optical 4f -setup with a reflective spatial frequency filter in the Fourier-plane for transverse mode selection. Driving the BALs with a high frequency modulated pump current above threshold active longitudinal mode-locking is achieved. Pulse durations as low as 88 ps are obtained, while the Gaussian-like fundamental or a higher order transverse mode up to mode number 5 is selected on purpose. Pulse duration and shape are nearly independent of the selected transverse mode.